Integrated assessment and management of public resources - Cooper, Joseph (Joseph C.), 1962-; Perali, Federico; Veronesi, Marcella, 1979-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2006)
This multidisciplinary work explores ways of making environmental policy decisions in managing public goods and natural parks with the goal of maximizing economic benefits to society. The contributors to the volume seek the best strategies for improving the environmental sustainability and quality of a public resource by showing how to develop quantitative information about the natural area and how it interacts with the economy. Such an analysis can be used to define policies that encourage interactions among institutions, local economic agents and park users. At the same time, it provides a measure to account for the implications of those policies on the local economy.
pt. 1. Assessment -- pt. 2. Management.
Includes bibliographical references and index.
Keywords: Natural resources, Communal -- Management; Public lands -- Management; Environmental economics; Electronic books